2018
DOI: 10.1103/physrevlett.120.221102
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter Equation of State through Cosmic History

Abstract: Cold dark matter is a crucial constituent of the current concordance cosmological model. Having a vanishing equation of state (EOS), its energy density scales with the inverse cosmic volume and is thus uniquely described by a single number, its present abundance. We test the inverse cosmic volume law for dark matter (DM) by allowing its EOS to vary independently in eight redshift bins in the range z ¼ 10 5 and z ¼ 0. We use the latest measurements of the cosmic microwave background radiation from the Planck sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 57 publications
2
43
0
Order By: Relevance
“…The value of w is negative because˜ c > c andh > h. This negative value indicates that dark matter is not formed by particles, for which w must lie between 0 (nonrelativistic limit) and 1/3 (ultrarelativistic limit) [31]. This value agrees with the results of [30], which analyzed the dark matter equation of state between z = 10 5 and z = 0 using the CMB and BAO data. Those results showed that w is consistent with 0 but allows a small negative value.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The value of w is negative because˜ c > c andh > h. This negative value indicates that dark matter is not formed by particles, for which w must lie between 0 (nonrelativistic limit) and 1/3 (ultrarelativistic limit) [31]. This value agrees with the results of [30], which analyzed the dark matter equation of state between z = 10 5 and z = 0 using the CMB and BAO data. Those results showed that w is consistent with 0 but allows a small negative value.…”
supporting
confidence: 82%
“…We use the cosmological constant as dark energy because it can naturally arise from the simplest Lagrangian for the gravitational field in which the torsion tensor is the only variable [29]. We show that dark matter satisfying an equation of state p = w [30], where p is the pressure and is the energy density, with w ≈ −0.01 instead of w = 0 removes the discrepancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the original GDM description also accounted for negative pressure and a nonvanishing viscosity c 2 vis;gdm . The effects of this modeling on the expansion and linear perturbations have been recently studied in [21][22][23][24][25][26]. Here we decided not to include the contribution of the viscosity c 2 vis;gdm since at the linear level it is degenerate with the sound speed c 2 s;gdm .…”
Section: Introductionmentioning
confidence: 99%
“…1, the equation of state parameter changes with the redshift and hence is time dependent. It turns out that the above problem of time dependent equation of state parameter is equivalent to that of an interacting dark energy fluid, which has been extensively studied in [28][29][30][31][32][33][34][35][36][37]. Using Monte Carlo Markov Chain technique one can demonstrate that models involving interacting dark energy (or, time dependent equation of state parameter) has degeneracy between the matter density and the dark energy interaction rate.…”
mentioning
confidence: 99%